The march of the brutes. Remarks on agential causes of the crisis of liberal democracy in Poland (De Legibus - Revista de Direito da Universidade Lusófona Lisboa, 2024)
In this short essay, we propose an alternative explanation for the current crisis of Western liberal democracies. Instead of focusing on economic factors, historical circumstances, or political narratives, we highlight the general attitudes of agents towards the law and the act of obeying legal rules. We argue that, at least in Poland, the decline of democratic institutions can be attributed to the emergence of a new, distinct type of public actors that are more aligned with the post-politics and post-truth era. We believe that our explanation can provide practical recommendations for those seeking effective solutions to the crisis.